P I – 3–10 Seasonal contrasts of indoor exposure to pm2.5 in peri-urban and urban beijing. (18th March 2018) - Hanbin, ZHANG; Fan, Yunfei; Han, Yiqun; Chan, Queenie; Yan, Li; Cai, Yutong; Zhou, Bingling; Krause, Anika; Chatzidiakou, Lia; Hu, Yongkai; Wu, Yangfeng; Jones, Rod; et al.
Abstract : Background/aim: Facing high concentrations of ambient air pollution and household air pollution from biomass burning, Beijing is introducing interventions on fuel for domestic heating in its strategy package. My study aims to: understand the indoor exposure to PM2.5 in peri-urban and urban Beijing during winter and summer, understand the causes of seasonal and spatial differences in indoor exposure levels. Methods: The Effects of AIR pollution on cardiopuLmonary disEaSe in urban and peri-urban reSidents in Beijing (AIRLESS) study, is a collaborative research project between UK and China to understand the health effects of air pollution in peri-urban and urban Beijing. During AIRLESS winter and summer campaigns, indoor deployment sub-panels were recruited out of the AIRLESS panels in peri-urban and urban Beijing. Urban sub-panel members were selected considering the floor of residence and distance to the main road; the selection criteria of the peri-urban sub-panel were: home exposure to environmental tobacco smoke (ETS), fuel used for cooking and fuel used for heating. RTI MicroPEM V3.2 nephelometer was deployed indoor to monitor PM2.5 continuously for at least 48 hours. Results: In this project, 25 peri-urban and 25 urban subjects completed more than 48 hour PM2.5 exposure monitoring for both winter and summer campaigns. In both peri-urban and urban sub-panels, there were significantly higher (p<0.01) log-transformed indoor exposure levels in winter than summer. When combining the subjects in the two sites together, the difference is till significant (p<0.01). Currently the effects of fuel types and air purifier on indoor air quality in peri-urban and urban Beijing are being investigated. Conclusion: This project shows that there are significant seasonal differences in indoor exposure levels to PM2.5 in AIRLESS peri-urban and urban sub-panels. Investigations will be conducted to analyse the reasons for seasonal and spatial differences, using the fuel, behaviour and air purifier data that were collected. In future, we hope to inform fuel use interventions and behaviour changes in Beijing.